Benirschke's Pathology of the Human Placenta - Baergen, Rebecca N.; Burton, Graham J.; Kaplan, Cynthia G.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book had its beginning in 1967 when Shirley G. Driscoll and Kurt Benirschke wrote in English the volume on placental pathology for the Henke-Lubarsch, the noted German Handbook of Pathology. There seemed to be a need for wider distribution of the text and it was reprinted by Springer Verlag, New York, essentially the only book available devoted just to the human placenta. Dr. Benirschke authored 5 subsequent editions in collaboration with Peter Kaufmann, Rebecca Baergen and Graham Burton in 1990 (2nd edition), 1995 (3rd edition), 2000 (4th edition), 2006 (5th edition) and 2012 (6th edition). In the early editions, the most important material was in a larger font than the extensive review of exceptions and the discussion in the literature. Since 1967, many other shorter placenta books have been published in English, French and German. None of these have included the breadth of discussion or the voluminous references which includes details of many historic articles, not readily available. Interest in the placenta has wildly expanded over the intervening 50+ years with the vast majority of Pathologists, Obstetricians and Pediatricians recognizing its value. In addition, there are now quite a few new journals, societies and meetings devoted to the placenta in both clinical and research areas. The interest extends into areas of study well beyond the realm of anatomic pathology. The 7th edition will, of necessity, differ from the prior editions which Dr. Benirschke wrote largely himself at first, and later with the help of the above noted co-authors. It will now be an international multi-authored book with nearly 40 contributors revising one or more chapters. The explosion of new information as necessitating some reordering of chapters and adding completely new chapters including Chapters 31 and 32, (3z(BInnovations in Placental Pathology(3y (Band (3z(BImaging in Placental Pathology(3y(B. Dr. Burton$1 (Bs section has been extensively edited, as well. The editors gave the new authors considerable latitude in how to write the new and/or edited chapters. Many of the revised chapters retain much of Dr. Benirschke$1 (Bs anecdotal information as well as the voluminous references. Others are more modern in their approach. All contain substantial new references and current information. It is our hope that Benirschke$1 (Bs Pathology of the Human Placenta will remain as a mainstay reference in placental pathology. It aims to help readers gain a broad understanding of how placental architecture is shaped during normal development, with a view to appreciating how this may be perturbed in complications of pregnancy.s
Examination of the Placenta -- Macroscopic Features of the Delivered Placenta -- Microscopic Survey -- Placental Types -- Early Development of the Human Placenta -- Basic Structure of a Placental Villus -- Architecture of the Villous Trees -- The Placental Bed -- The Placental Circulations -- The Chorionic and Basal Plates -- Approach to Histologic Examination of the Placenta -- Abortion and Chromosomal Anomalies -- Abnormalities in Implantation -- The Placenta Accreta Spectrum -- Anatomy and Pathology of the Placental Membranes -- Anatomy and Pathology of the Umbilical Cord -- Placental Shape Aberrations -- Multiple Pregnancies -- Maternal Vascular Malperfusion and Associated Maternal Diseases -- Maternal Diabetes and Obesity -- Other Maternal Disorders Complicating Pregnancy -- Fetal Vascular Malperfusion -- Erythroblastosis Fetalis, Hydrops Fetalis and Transplacental Hemorrhage -- Fetal Storage Disorders -- Infectious Diseases -- Placental Disorders of Uncertain Etiology -- Placental Mesenchymal Dysplasia -- Molar Pregnancies -- Gestational Trophoblastic Neoplasms -- Chorangiotic Lesions, Benign Tumors, and Heterotopias -- Innovations in Placental Pathology -- Imaging of Placental Pathology -- Assisted Reproductive Technologies -- Legal Considerations.
Keywords: Pathology; Midwifery; Pathology; Midwifery; Placenta -- pathology; Placenta Diseases